Biological Flora of the British Isles: Lathraea clandestina. (14th August 2020) - Atkinson, Mark D.; Atkinson, Elaine
Abstract: This account presents information on all aspects of the biology of Lathraea clandestina L. (Purple Toothwort) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles : distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, hervbivores and disease, history and conservation. Lathraea clandestina is a holoparasitic perennial herb essentially devoid of chlorophyll which can parasitize a wide range of host plants. These include ferns, herbs and trees although it is most frequent on Populus spp., Salix spp. and Alnus glutinosa . It usually flowers between April and June. It is pollinated principally by long‐tongued bumblebees ( Bombus spp.). The flowers arise directly from a subterranean stem and have specialised features to reduce nectar theft particularly by ants and birds. Seeds are explosively ejected and can spread up to 8 m. For most of the year, plants are not visible. Lathraea clandestina is native to Belgium, throughout much of western France as far north as Brittany, Andorra, the Pyrenees in France and Spain, northern Spain and in Italy where it has a very disjunct distribution. It has been widely introduced in Britain and Ireland and is extensively naturalised. It has been introduced and naturalised also in The Netherlands, Switzerland and Germany. It is very commonly a riparian plant and can spread downstream. As a parasite dwelling underground for most of the year, L. clandestina draws solutes from the xylem of the host root using hydathode glands on the inner surface of the scales. Consequently a stream of liquid is exuded which affects surrounding vegetation. Lathraea clandestina still exhibits vestiges of some of the enzyme activity associated with photosynthesis and has a very limited ability to assimilate inorganic nitrogen and carbon. Its chloroplast genome is less reduced than in many other holoparasitic plants. Abstract : Purple toothwort is widely planted and naturalised in the British Isles, but is native to Belgium, France, Spain and Italy. It is a parasitic herb which lives underground for most of the year. Only the flowers and the tips of the shoots are visible for about 3 months. The flowers arise just above ground level and are pollinated mostly by bumblebees, and it disperses seeds explosively. It is parasitic on a range of woody and herbaceous plants but in the British Isles, it is most frequent on poplars and willows, particularly along watercourses.